2013
DOI: 10.1016/j.jim.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Invasive African nontyphoidal Salmonella requires high levels of complement for cell-free antibody-dependent killing

Abstract: Nontyphoidal isolates of Salmonella (NTS), particularly Salmonella Typhimurium, are a major cause of invasive bacteremia in Africa. Despite this, no vaccine against NTS is currently available for use in humans. If a NTS vaccine is to be developed in a timely manner, there is a need to develop assays to assess its in vivo efficacy. Assessment of potential efficacy of candidate vaccines in preclinical models is important for proof-of-concept and reduces attrition of vaccines in clinical trials. Serum bactericida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…This indicates that st313-td influences the uptake and/or early survival in macrophages but only in activated cells. Notably, in a previous study it was demonstrated that S. Typhimurium D23580, assigned to ST313 and carrying st313-td requires high levels of complement for antibody-mediated bactericidal activity compared with S. Typhimurium LT2 [19]. Thus, st313-td might play a role in virulence by either decreasing the binding of the bacteria to antibodies causing less uptake in macrophages or by diminishing the susceptibility to complement mediated lysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that st313-td influences the uptake and/or early survival in macrophages but only in activated cells. Notably, in a previous study it was demonstrated that S. Typhimurium D23580, assigned to ST313 and carrying st313-td requires high levels of complement for antibody-mediated bactericidal activity compared with S. Typhimurium LT2 [19]. Thus, st313-td might play a role in virulence by either decreasing the binding of the bacteria to antibodies causing less uptake in macrophages or by diminishing the susceptibility to complement mediated lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Gallinarum [10]. For these reasons, S. Typhimurium ST313 D23580 has been extensively used in studies on host pathogen interaction to gain more knowledge about NTS infection and to elucidate the reason for the apparent increased pathogenicity of this clone [15][19]. Some of these studies suggest that S. Typhimurium ST313 might have adapted to occupy an ecological and immunological niche provided by HIV, malaria and malnutrition in Africa [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have successfully used 3-to 4-week-old baby rabbit complement (BRC) in SBA assays to evaluate S. Typhi vaccines (23,24). Similarly, BRC was employed in an S. Typhimurium SBA assay, although very high concentrations (75%) of complement were required to mediate killing by the antibody (25). While these assays have allowed the demonstration of SBA responses against S.…”
mentioning
confidence: 99%
“…Typhi, S. Paratyphi A, and S. Typhimurium, no assay has been reported to determine SBA responses against S. Enteritidis (14,(23)(24)(25). Furthermore, none of these assays has been standardized to measure vaccine-induced endpoint SBA responses against Salmonella serovars.…”
mentioning
confidence: 99%
“…Microheterogeneities in the polysaccharide compositions of LPSs have been described even within the same serotype (36), and it is possible that such variations affect antibody binding and function, especially since the exact epitope to which antibody binds may alter bactericidal activity (5,8). In this context, it may be relevant that recent experiments have shown that antibody-mediated killing of the S. Typhimurium isolate used to assess bactericidal activity in the Malawi study required unusually large amounts of complement (37). This characteristic may also contribute to the differences from our results.…”
Section: Discussionmentioning
confidence: 99%